Characteristics of Parental Communication as a Factor of Adolescents' Psychological Well-Being - Ermolaeva M.V (Moscow State University of Psychology and Education, 2020)
The paper presents results of a study on the relationship between psychological well-being of adolescents and features of their parents' communication. The study involved 92 subjects: 46 adolescents aged 13-14 years, studying in one of the Moscow schools, and their mothers (46 females). The adolescents' psychological well-being was measured with the Piers-Harris Self-Concept Scale (scales VI, VII and VIII), the Warwick-Edinburgh Mental Well-Being Scale, and with the questionnaire by I.М. Markovskaya. Features of parental communication were assessed using the social skills questionnaire by V.F. Ryakhovskiy, the Self-Monitoring Scale by M. Snyder, and the Questionnaire Measure of Emotional Empathy by A. Mehrabian and N. Epstein. The study revealed a five-factor structure of psychological well-being of the adolescents and of their perception of childparent relations. It showed a correlation between the level of parental emotional response and the adolescents' assessments of consent in their relationships with the parents. The adolescents' satisfaction with communication with peers was also related to their parents' social skills. Low and pronounced communicative skills of the parents are associated with high and average levels of adolescent satisfaction with peer communication respectively; normal communicative skills in the parents is associated with low satisfaction in the adolescents. The paper concludes with a discussion on the application of the obtained results in psychological counseling and psychological education of parents.